Effect of milling on the color, nutritional properties, and antioxidant contents of glutinous black rice - Thunnop Laokuldilok (2018)
Dehulled glutinous black rice (cv. Kam Doi Saket) was abrasively milled (0-60 s) to make a degree of milling (DOM) curve. The curve showed a nonlinear relationship between milling time and DOM. The slope sharply increased in the first 20 s; after this point, the increase was moderate. The redness of grain and flour surprisingly increased after milling, and the highest value was found at 20 s of milling. Protein, fat, and crude fiber were not uniformly distributed in the dehulled rice kernel. The rice retained only 76.95, 32.79, 20.24, and 36.57% of protein, fat, crude fiber, and ash, respectively, after milling for 60 s. Anthocyanins, γ-oryzanol, and α-tocopherol decreased by 74.49, 55.35, and 70.36%, respectively, after 10 s of milling. The scavenging activity decreased sharply when milling was carried out for longer than 30 s. The methanolic extract from rice milled for 60 s showed the lowest activity, which was 21.1 times lower than that of the dehulled rice extract. It was concluded that milling for 20 s was sufficient to remove most of the bran layer of the black rice sample, but 10 s of milling retained higher contents of nutritional components and rice antioxidants. © 2013 AACC International, Inc.